Continuous cement leakage along the posterior longitudinal ligament of the intraspinal epidural during a percutaneous vesselplasty: A case report and literature review - An, Ning; Guo, Sijia; Lin, Jisheng; Zhuang, Haoxiang; Meng, Hai; Su, Nan; Fei, Qi (Frontiers in Surgery, 2023)
Objective This study aims to report one case of intraspinal epidural cement leakage caused by a novel percutaneous vesselplasty. Methods A clinical case report from the Orthopedic center of our hospital and a literature review. A 63-year-old woman with an L2 osteoporotic compression fracture underwent novel kyphoplasty, percutaneous vesselplasty. This rare complication was evaluated through a literature search, and its special types are classified in more detail. Results The patient was hospitalized with low back pain two weeks after a fall. After auxiliary examination, a new type of percutaneous vesselplasty was performed. After the intraoperative injection of bone cement, bone cement leakage extended along the posterior longitudinal ligament and epidural space. There were no special compression symptoms of the spinal cord, and the prognosis of conservative treatment was good. Conclusion Although percutaneous vesselplasty is relatively safe and frequent, intraspinal leakage may occur, so sufficient preoperative evaluation, intraoperative continuous fluoroscopic monitoring, and timely evaluation of postoperative images are extremely necessary.